Shattered thyroid gland in a young boy after a blunt neck trauma - Khim, Soon Vong; Mohamad, Irfan; Mohamad, Hazama; Zakaria, Zaidi (Elsevier, 2016)
Blunt thyroid injury in motor vehicle accident in paediatric patient is relatively rare. The symptoms are often barely anterior neck swelling which gradually increases in size and may or may not compromise the airway, and it can be fatal if missed to be identified. We described the case of a 15-year-old boy who involved in an accident and sustained a shattered thyroid gland despite no open wound in the neck. The management issues were outlined.